2010
DOI: 10.1164/rccm.200911-1757oc
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor–1 Levels Contribute to the Development of Bacterial Translocation in Sepsis

Abstract: Rationale: Many lines of evidence point toward the gastrointestinal (GI) tract in the pathophysiology of organ dysfunction in sepsis. Splanchnic hypoperfusion during sepsis leads to enterocyte apoptosis, diminished barrier function, and release of bacterial products. Sepsis lowers levels of insulin-like growth factor (IGF)-1, a known antiapoptotic factor. We recently demonstrated that treatment with IGF-1 is protective in murine sepsis. Objectives: We hypothesize that decreased IGF-1 levels in sepsis contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 51 publications
0
37
0
1
Order By: Relevance
“…The number of specific bacterial groups was determined by using a StepOnePlus real-time PCR system (Applied Biosystems 7300). The sequences of specific bacterial primers were as previously published (14).…”
Section: Experimental Design (I) Experimentsmentioning
confidence: 99%
“…The number of specific bacterial groups was determined by using a StepOnePlus real-time PCR system (Applied Biosystems 7300). The sequences of specific bacterial primers were as previously published (14).…”
Section: Experimental Design (I) Experimentsmentioning
confidence: 99%
“…IGF-1 can prevent intestinal atrophy in septic rats and protect the integrity of intestinal structure (11,12,13,18,21). Gary et al reported that the development of bacterial translocation is inversely correlated with serum IGF-1 levels and treatment with IGF-1 decreased enterocyte apoptosis (19). Thus, GH improves the impairment of the intestinal mucosa and maintains the structure and function of the intestinal mucosal barrier (12)(13)(14)20).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of IGF were previously demonstrated in patients with sepsis [64]. Additionally, a decline in IGF1 level was inversely correlated with the degree of bacterial translocation across the gastrointestinal epithelium in patients with gram-positive sepsis [63]. …”
Section: Management Of Organism and Organism Toxicity In Septic Shockmentioning
confidence: 92%
“…Drugs associated with intestinal barrier protection, antiapoptotic properties, and/or protection against increases in intestinal permeability, such as IL-11 [62] and insulin-like growth factor (IGF) [63], have been analyzed in preclinical studies. Reduced levels of IGF were previously demonstrated in patients with sepsis [64].…”
Section: Management Of Organism and Organism Toxicity In Septic Shockmentioning
confidence: 99%